Model Pembelajaran Shooting Sepakbola Berbasis Permainan Untuk Siswa SMP di Kota Gorontalo - Dahrianto; Aisah R. Pomatahu; Mirdayani Pauweni; Rosbin Pakaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop a football shooting learning model based-game for students at SMP Negeri 6 and SMP Negeri 12 in Gorontalo City. It applies the six stages of development research adopted from Borg and Gall’s 10-step research and development model, namely: analysis of potential problems, initial product design, design validation and revision, small-scale testing and design revision, large-scale testing and design revision, and effectiveness testing. Based on this sequence of stages, the following results were obtained: (1) an average score of 4.53 for the initial version of the game-based shooting learning model, which required revision before the small-scale trial; (2) 17 out of 20 students responded well or very well during the small-scale trial; (3) 27 students responded well or very well, while 21 students responded fairly to very poorly in the large-scale trial, (4) the learning model is effective in improving students’ shooting skills. Based on these findings, it can be concluded that the developed learning model, in addition to being innovative, is also effective for application in teaching football-related material. Keywords: Learning Model, Physical Education, Shooting, Football, Junior High School